ANTI-HIV DAN SUBTIPE HIV PADA PASIEN HEMODIALISIS - Retno Handajani; Mochammad Thaha; Mochamad Amin; Citrawati Dyah Kencono Wungu; Edhi Rianto; Pranawa Pranawa (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Anti-Human Immunodeficiency Virus (Anti-HIV) was performed from 100 plasma Chronic Kidney Disease (CKD) stage 5 patientswith continuous hemodialysis (HD) at the Hemodialysis Instalation Dr Soetomo hospital, Surabaya, Indonesia, using three (3) kind ofreagents: Tri-line HIV Rapid test Device from Acon for HIV 1/2/O as strips form, Foresight HIV 1/2/O Antibody EIA Test Kit from Aconand Anti-HIV 1+2/Subtype O ELISA from Axiom. HIV RNA and HIV subtype were detected by Reverse Transcription Polymerase ChainReaction (RT-PCR) based on HIV gag region and analysis of DNA result. Seventy three % patients were hemodialysed twice in a week andonly 14% with duration more than five (5) years. Most of the patients (43%) were hemodialysed between 100−300 times. From the 100plasma samples was obtained only one (1%) man patient plasma sample with positive anti-HIV. A weak positive of RT-PCR result wasnot succeed to be sequenced for determining the HIV subtype. This cause was suspected due to low levels of HIV RNA in blood. The resultsof this study was expected can be used as an additional management consideration of hemodialysis patients at the Hemodialysis Unit.